IMPLEMENTASI KEBIJAKAN INOVASI PELAYANAN PUBLIK DI PUSKESMAS JAYA MUKTI DALAM MENINGKATKAN KEPUASAN MASYARAKAT - saputra, trio; marlinda, pebriana; sufi, wasiah (Jurnal Niara, 2019)
Public service innovation policies are still new in the implementation of public services at this time. Puskesmas Jaya Mukti is one of the government institutions that innovates through the Optima cycle. The research method used is a qualitative approach, analysis of interactive models and interactive analysis in various qualitative analyzes as a continuous, repetitive and continuous effort. The results of the study showed that the policy implementation of the Proven Health Center using the Optima Cycle had gone well, automatically not making the patient's satisfaction in the Puskesmas increased. The inhibiting factors of the application of cyclical optima are the length of the report download from sikda optima, and in the application of the cyclical optima application there is still no recapitulation of the patient's history below 2016. And the latter requires a supportive policy such as the policy generator used to turn off the lights.